Clinical features and prognostic impact of PRDM16 expression in adult acute myeloid leukemia. Issue 11 (11th August 2017) - Yamato, Genki; Yamaguchi, Hiroki; Handa, Hiroshi; Shiba, Norio; Kawamura, Machiko; Wakita, Satoshi; Inokuchi, Koiti; Hara, Yusuke; Ohki, Kentaro; Okubo, Jun; Park, Myoung‐Ja; Sotomatsu, Manabu; et al.
Abstract: High PRDM16 (also known as MEL1 ) expression is a representative marker of acute myeloid leukemia (AML) with NUP98‐NSD1 and is a significant predictive marker for poor prognosis in pediatric AML. However, the clinical features of adult AML with PRDM16 expression remain unclear. PRDM16 is highly homologous to MDS1/EVI1, which is an alternatively spliced transcript of MECOM (also known as EVI1 ). We investigated PRDM16 expression in 151 AML patients, with 47 (31%) exhibiting high PRDM16 expression ( PRDM16/ABL1 ratio ≥ 0.010). High PRDM16 expression significantly correlated with DNMT3A (43% vs. 15%, P < 0.001) and NPM1 (43% vs. 21%, P = 0.010) mutations and partial tandem duplication of KMT2A (22% vs. 1%, P < 0.001). Remarkably, high‐ PRDM16 ‐expression patients were frequent in the noncomplete remission group (48% vs. 21%, P = 0.002). Overall survival (OS) was significantly worse in high‐ PRDM16 ‐expression patients than in low‐ PRDM16 ‐expression patients (5‐year OS, 18% vs. 34%; P = 0.002). This trend was observed more clearly among patients aged <65 years (5‐year OS, 21% vs. 50%; P = 0.001), particularly in FLT3 ‐ITD‐negative patients in the intermediate cytogenetic risk group (5‐year OS, 25% vs. 59%; P = 0.009). These results suggest that high PRDM16 expression is a significant predictive marker for poor prognosis in adult AML patients, similar to pediatric AML patients.